Trial Watch: Immunostimulatory monoclonal antibodies for oncological indications. (2nd December 2017) - Cabo, Mariona; Offringa, Rienk; Zitvogel, Laurence; Kroemer, Guido; Muntasell, Aura; Galluzzi, Lorenzo
ABSTRACT: The goal of cancer immunotherapy is to establish new or boost pre-existing anticancer immune responses that eradicate malignant cells while generating immunological memory to prevent disease relapse. Over the past few years, immunomodulatory monoclonal antibodies (mAbs) that block co-inhibitory receptors on immune effectors cells – such as cytotoxic T lymphocyte-associated protein 4 (CTLA4), programmed cell death 1 (PDCD1, best known as PD-1) – or their ligands – such as CD274 (best known as PD-L1) – have proven very successful in this sense. As a consequence, many of such immune checkpoint blockers (ICBs) have already entered the clinical practice for various oncological indications. Considerable attention is currently being attracted by a second group of immunomodulatory mAbs, which are conceived to activate co-stimulatory receptors on immune effector cells. Here, we discuss the mechanisms of action of these immunostimulatory mAbs and summarize recent progress in their preclinical and clinical development.